Preparation of cellulose-based fluorescent carbon nanoparticles and their application in trace detection of Pb(ii). Issue 5 (12th January 2017) - Yun-fei, Zhang; Maimaiti, Halidan; Bo, Zhang
Abstract : Nanocrystalline cellulose (NCC) with a particle size of 23.80 ± 0.33 nm was prepared from microcrystalline cellulose by a mixed treatment with acids and ultrasound. Abstract : Nanocrystalline cellulose (NCC) with a particle size of 23.80 ± 0.33 nm was prepared from microcrystalline cellulose by a mixed treatment with acids and ultrasound. The NCC was chlorinated with thionyl chloride, submitted to dehydrating carbonization and oxidization, and then modified with ethylenediamine (EDA) to obtain fluorescent carbon nanoparticles (NCC–EDA). These were characterized by elemental analysis, TEM, BET, FT-IR, XRD, TG-DTA, XPS, UV-Vis, and photoluminescence. It was found that NCC–EDA were vesicle-like porous particles formed through the linking and intertwining effects of EDA on the SOCl2 -treated NCC. The surface of NCC–EDA is rich in oxygen-, nitrogen- and sulfur-containing functional groups, and the particle size was 41.45 ± 0.55 nm. This endows the NCC–EDA with good dispersity in water, high absorbance and strong fluorescence. The NCC–EDA are shown to be viable probes in that their fluorescence is selectively quenching by Pb(ii ). The findings were exploited to design a fluorometric assay for Pb(ii ) that has a 24 nM detection limit.